The Low Birth Weight Infants - Aliamran Rasjid; H.E Monintja; Rachmat Sadeli; Amat Kuat (Paediatrica Indonesiana, 1979)
A study on 1045 low-birth-weight infants born in the Dr. Cipto Mangunkusumo General Hospital, Jakarta, between January 1975 and December 1976 was conducted; exogenous factors that may influence birth weight were statistically analyzed.